A sense of place within landscape cultural settings / Nik Mastura Nik Mohammad … [et al.] - Nik Mohammad, Nik Mastura; Saruwono, Masran; Said, Shahrul Yani; Wan Hariri, Wan Ahmad Halawah (Universiti Teknologi MARA Cawangan Selangor, 2018)
This paper presents an on-going progress of a study on landscape elements in the context of culture. The study has sought to discover people’s perception, experience and responses towards their surroundings based on elements that relate to their culture and norms. Eventually, new developments do not seem to recognize and respect the importance of cultural aspects resulting disoriented buildings. An extensive reviewed of the literature was conducted to rediscover the fundamental notions of place, perception and experience. Therefore, the background review to structure the work concluded places that add value contribute to establish the urban setting and place context.